Microsoft Windows 7 - Bruzzese, J. Peter; Safari eBooks ([Indianapolis, Ind.] : Que, 2009)
"In Windows 7: Video LiveLessons, J. Peter Bruzzese presents more than six hours of personalized Windows 7 video training - 100 quick, bite-size video lessons that teach virtually every essential skill Windows 7 users want and need. You can build your skills one step at a time, by simply watching these polished, upbeat videos" --Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
"Video Sneak Peeks are available exclusively to Safari Books Online subscribers and contain pre-production footage in a sometimes rough, incomplete format" --Resource description page.
Title and publication data from resource description page (viewed Aug. 22, 2009).
Electronic reproduction.
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Electronic books